Barcelona, Beijing, Birmingham: Populism and English Art Schools in Transition. Issue 5 (2nd November 2018) - Harris, Jonathan
Abstract : This article considers the impact of a range of contemporary political factors on the future role and status of English art schools, with a focus on questions of diversity, international student recruitment, globalisation and curriculum development. These factors primarily comprise: the Brexit vote in 2016, the UK government's related hostility to international student recruitment (based on the erroneous idea that these students are surreptitious migrants), the election of Trump and the ambiguous rise of populisms on the left and right. Given the turmoil already present in the UK university system – related to the raising of fees and the creation of an apparently consumerist 'Office for Students' replacing the Higher Education Funding Council for England – how have art schools responded to this crisis in the purpose of education, the role of contemporary art and its place in and as part of globalised a world?